2004
DOI: 10.1002/app.13485
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(III)‐mediated microemulsion polymerization of acrylonitrile: Kinetics and particle morphology

Abstract: ABSTRACT:The catalytic effect of trans-dichloro-bis(ethylenediamine)cobalt(III) chloride (trans-[Co(en) 2 Cl 2 ]Cl) complex on the microemulsion polymerization of acrylonitrile, in the absence of added emulsifier, was investigated. Polymerization was studied at varying concentrations of initiator, monomer, complex, and solvent over the temperature range of 30 -70°C. The overall activation energy (E a , 39.26 kJ/mol), energy of dissociation of initiator (E d , 61.62 kJ/mol), number of micelles (0.122 ϫ 10 18 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As 13 From the experimental data, it was observed that particle size increased with the increase in concentration of complex, as shown in Table 2. However, it is suggested that the polymerization was stabilized by the presence of the complex, with reduction of the particle size into the nano-range, which was further confirmed from TEM figure.…”
Section: Variation Of [Co(iii)(en) 2 CL 2 ]Cl Concentrationmentioning
confidence: 81%
“…As 13 From the experimental data, it was observed that particle size increased with the increase in concentration of complex, as shown in Table 2. However, it is suggested that the polymerization was stabilized by the presence of the complex, with reduction of the particle size into the nano-range, which was further confirmed from TEM figure.…”
Section: Variation Of [Co(iii)(en) 2 CL 2 ]Cl Concentrationmentioning
confidence: 81%
“…So in the present study, an attempt has been taken to highlight these aspects and to prepare PAN/SS nanocomposite via a nonconventional method in the absence of surfactant or emulsifier under the catalytic effect of an in situ developed transition metal complex Cu(II)/ glycine. Nonconventional method of synthesis of various polymers under the catalytic effect of in situ developed and also isolated complex of transition metals have already been reported [26][27][28][29] in our earlier publications. Thus the most significant outcome of the paper is the conversion of the nonbiodegradable hydrophobic homopolymer PAN into the biodegradable hydrophilic material via the application of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%